The Impact Of Online Loans On People Lifestyles - Soukotta, Agnes; Lusiana Yulianti, Maria; Nindya Putri, Andiena (Journal of Management, 2024)
This study examines how internet loans affect people's lifestyles in Indonesia. This study included 155 Indonesian residents who were selected using quantitative methods such as multiple linear regression analysis techniques. Secondary and primary data were used to evaluate hypotheses, with multiple linear regression tests being performed. The findings of the study show that both online loans and financial literacy have a positive and significant impact on lifestyle. Financial literacy also has a positive and significant impact on lifestyle, and online loans have a positive and significant impact on the lifestyle of Indonesians.